KORELASI SERUM AMYLOID A (SAA) DENGAN KADAR TROPONIN I PADA PASIEN SINDROMA KORONER AKUT DI RSUP DR.SARDJITO YOGYAKARTA - , NADIA AYU SAFITRI, Dr. Setyawati, Sp.PK(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Acute Coronary Syndrome (ACS) is a multifactorial disease and occurs in response inflammation, plaque rupture and cause thrombosis of blood vessels either in total or in part. Biomarkers play an important role in the diagnosis and treatment will be given. Serum amyloid A is an acute inflammasi marker that acts to stimulate the expression of matrix degrading enzymes that can cause plaque rupture. Troponin I is a marker of heart muscle damage due to necrosis. Objective : to known the correlation between serum amyloid A and Troponin I levels in patients with Acute Coronary Syndrome . Methods : The study design was a cross sectional study of patients with acute coronary syndrome subjects received treatment in ICCU Hospital Dr.Sardjito. Examination of SAA was measured by sandwich ELISA method whereas Troponin-I conducted by ELISA using a VIDAS Troponin I Ultra then analyzed with Spearman's test. Results : There were 33 patients withACS . From the analysis of the data using the Spearman test ,there are not significant correlations between the SAA and Troponin I in patient with ACS (r=0.6, p=0.74). Conclusions : There are not significant correlation between SAA and Troponin I in patients with ACS in ICCU Dr . Sardjito Yogyakarta.